Impact on quality of life from multimodality treatment for lung cancer: a randomised controlled feasibility trial of surgery versus no surgery as part of multimodality treatment in potentially resectable stage III-N2 NSCLC (the PIONEER trial). (15th July 2021) - Taylor, Sally; Yorke, Janelle; Tsim, Selina; Navani, Neal; Baldwin, David; Woolhouse, Ian; Edwards, John; Grundy, Seamus; Robson, Jonathan; Rhodes, Sarah; Gomes, Fabio; Blackhall, Fiona; et al.
Abstract : Introduction: Optimal treatment for 'potentially resectable' stage III-N2 non-small cell lung cancer (NSCLC) requires multimodality treatment: local treatment (surgery or radiotherapy) and systemic anticancer therapy. There is no clear evidence of superiority for survival between the two approaches and little research has explored quality of life (QOL). This study will inform the design of a phase III randomised trial of surgery versus no surgery as part of multimodality treatment for stage III-N2 NSCLC with QOL as a primary outcome. Methods and analysis: Patient participants will be randomised to receive multimodality treatment (1) with surgery OR (2) without surgery. The Quintet Recruitment Intervention will be used to maximise recruitment. Eligible patients will have 'potentially resectable' N2 NSCLC and have received a multidisciplinary team recommendation for multimodality treatment. Sixty-six patients and their carers will be recruited from 8 UK centres. Patient/carer QOL questionnaires will be administered at baseline, weeks 6, 9, 12 and month 6. Semistructured interviews will be conducted. Quantitative data will be analysed descriptively and qualitative data will be analysed using framework analysis. Ethics and dissemination: Ethical approval has been obtained. Results will be disseminated via publications, national bodies and networks, and patient and public involvement groups. Trial registration: NCT04540757